Mobile Legend Bang Bang: Level Of Confidence Of E-Sport Athlete - Septiana, Rama Adha (Journal Coaching Education Sports, 2023)
There are many feelings of not being confident about playing the game in its best condition. Athletes often complain about training or during matches, especially e-sports athletes. This study aims to determine the confidence of MLBB esport athletes. This research is a quantitative descriptive research. The method used in this study was a survey method and data collection techniques using a questionnaire which was distributed via Google form. The population in this study were experienced esport athletes who are domiciled in Bandung, Cimahi and its surroundings. This study uses a convenience sampling technique. The sample of this study was 43 people who were representatives of every sport who agreed and wanted to provide the information needed. The instrument used in this study was a questionnaire on the confidence level of MLBB esport athletes. Data analysis used a descriptive method with percentage calculations. The results of the study show that the confidence level of these MLBB esport athletes is at a high level of 80%. And based on internal factors, MLBB esport athletes are included in the "High" category, while based on external factors, they are included in Moderate. While the results of the analysis of the data obtained by the confidence of esport athletes are not lower at the level of confidence.